1982
DOI: 10.1038/bjc.1982.35
|View full text |Cite
|
Sign up to set email alerts
|

Blood basophils in lung cancer

Abstract: Summary.-Peripheral-blood basophils were counted, in thick smears, in samples from patients with primary bronchial carcinoma, from patients in the same wards and from normal individuals. The median counts for patients with other chest conditions (15-5/4d) and bronchial-carcinoma patients free of tumour months to years after resection (16/1l) did not differ from those for normal individuals (19/1,u), but tumour-bearers showed higher counts (median 33/1z), 24/41 having counts above the highest count in normal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Basophils are known to be involved in immediate hypersensitivity and cutaneous basophil hypersensitivity. Anthony (1982) demonstrated that basophil counts were elevated in patients with squamous bronchial carcinoma and caused worse clinical conditions. Classical inflammatory monocytes and their derivative macrophages promote tumor metastasis (Cassetta and Pollard, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Basophils are known to be involved in immediate hypersensitivity and cutaneous basophil hypersensitivity. Anthony (1982) demonstrated that basophil counts were elevated in patients with squamous bronchial carcinoma and caused worse clinical conditions. Classical inflammatory monocytes and their derivative macrophages promote tumor metastasis (Cassetta and Pollard, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…De Monte et al (47) revealed that the infiltration of BAs in tumor-draining lymph nodes was associated with the Th2/Th1 cell ratio in tumors and was responsible for the presence of IL-4 in pancreatic cancer. In addition, the counts of circulating BAs in patients with non-small cell lung cancer were higher compared with in healthy individuals (50). Furthermore, in a mouse model of metastatic breast cancer generated by implanting 4T1 cells into the mammary fat pads, Wang et al (21) reported that circulating BAs were negatively associated with the number of lung metastases.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…Increased basophil counts have been reported in hematologic and solid tumors . However, the role of circulating and tissue resident basophils in human and experimental cancer is almost unexplored in the vast majority of tumor types.…”
Section: Role Of Mast Cells and Basophils In Health And Diseasementioning
confidence: 99%
“…Increased basophil counts have been reported in hematologic [461][462][463] and solid tumors. 464 However, the role of circulating and tissue resident basophils in human and experimental cancer is almost unexplored in the vast majority of tumor types. Basophils infiltrate human gastric mucosa of Helicobacter pylori-infected patients affected by severe gastritis and cancer.…”
Section: Basophils and Cancermentioning
confidence: 99%